Social support and quality of life in migrant workers: Focusing on the mediating effect of healthy lifestyle - Yang, Yufan; Zhao, Shuzhen; Lin, Lulu; Qian, Jieyu; Zhang, Haiyan; Cai, Fuman (Frontiers in Public Health, 2023)
Objective: To investigate the relationship between social support and quality of life of Chinese migrant workers and to explore the mediating role of healthy lifestyles in social support and quality of life. Methods: Using a stratified multi-stage sampling method, 1298 migrant workers and 983 urban workers across 110 neighborhood committees in five economic development zones in eastern China were surveyed. The social support level of participants was quantified using the Social Support Rating Scale, and quality of life was evaluated using the SF-8. Healthy lifestyle was evaluated based on a combination of sleep, smoking, alcohol consumption, and exercise. Multiple linear regression analysis was used to assess the relationship between quality of life and social support. Stepwise regression was used to analyze the mediating effect of healthy lifestyle, social support, and quality of life among migrant workers. Results: Total SSRS and total SF-8 scores of migrant workers were significantly higher than those of urban workers (P<0.001). After controlling for confounders, social support showed an independent positive association with quality of life for both migrant (β = 0.50, P<0.05) and urban workers (β = 0.62, P<0.05). Mediation effect analysis revealed that healthy lifestyle partially mediated the relation between social support and quality of life of migrant workers with a mediation effect of 0.07, accounting for 11.70% of the total effect. Conclusions: This study showed a significant correlation between social support and quality of life of Chinese migrant workers, with healthy lifestyle playing a mediating role. Improving the social support and health literacy of migrant workers and developing a healthy lifestyle are key to improving their quality of life.